Cyclometalated palladium(II)-catalyzed asymmetric C-C and C-P bond formation reactions - Gan, Kennard Jun Hao (2016)
The first part of this thesis aims to provide an account of the synthetic strategies employed for the asymmetric formation of novel ferrocenyl monophosphine ligands. It also attempts to justify the observed stereoselectivities with mechanistic models. Following which, the second part of the thesis comprises the successful application of cyclometalated Palladium(II)-complexes as catalysts toward aryl boronic acid addition onto a variety of unsaturated enones.